PENGARUH BAHASA DALAM TUMBUH KEMBANG ANAK USIA DINI - Purwati, Purwati (Universitas Muhammadiyah Magelang, 2009)
Play and children is a unity that can not be separated. Play activities and activities children do children always show play activities. Play and children are closely linked. Therefore, one of the principles of learning in early childhood education is to play and learn. Playing is part of the development, sense of self, social and physical capacity. At the same time, through play, the children direct (direct) of their energy to do activities that they choose. These activities stimulate further development. Play is essential for the development and early childhood learning in order to develop optimally. A combination of playing characteristics and the characteristics of the child provides an energy that encourages the development of the primary needs of children. Thus, an educator at both school and parents as educators in the home should play know essence and requirements contained in them so the children there is an optimal development.